Numerical modeling of new Ductile concrete material as infill wall - Tiam shirzadi (Numerical Methods in Civil Engineering)
In urban construction, the prevalent use of reinforced concrete (RC) with masonry infill is challenged by the brittle nature of traditional masonry, which significantly increases seismic vulnerabilities. This research introduces a novel solution: Ductile Lightweight Fiber-Reinforced Concrete (DLFC) as an infill material. DLFC is composed of cement, water, expanded polystyrene (EPS), ultra-fine fillers, and a blend of polyvinyl alcohol (PVA) and polypropylene (PPF) fibers. The primary goal of using DLFC is to enhance ductility, reduce damage during seismic events, and improve energy absorption capabilities. One of the most important concerns of engineers is how to model the walls and its effects on the structure. In this study, the method of modeling the experimental element was discussed first, and then its effects on the structure were discussed with numerical modeling in the form of finite element and macro model. The analysis performed is a non-linear time history analysis, which was compared according to the bare and infill frame with DLFC blocks in SAC structures. The results show a decrease in the displacement of the roof of the structure and non sensational shift of period in structures.